Innovations to improve quality in dairy value chains - Van Campenhout, Bjorn; Kariuki, Sarah; Ario, Richard; Chamberlin, Jordan; Vudriko, Patrick (International Food Policy Research Institute, 2023)
This is a presentation done for the Rethinking Markets Science Session on September 7th 2023.